DOI: 10.14264/uql.2017.61
|View full text |Cite
|
Sign up to set email alerts
|

Improving research outcome measurement in aphasia: Development of a core outcome set

Abstract: Aphasia treatment research lacks a consistent approach to outcome measurement. There is heterogeneity in the outcome measures used across treatment trials and a lack of research evidence exploring the outcome constructs which are most important to key stakeholders. The efficiency, relevancy, transparency, and overall quality of aphasia treatment research could be increased through the development of a core outcome set (COS)-an agreed standardised set of outcomes for use in treatment trials. The overarching aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In addition, as previously mentioned, this study is restricted to measures available in the database, which shaped the approach of dividing by WAB-R subtype. Although we recognize the limitations of the WAB-R, using it as a lens through which to examine differences associated with specific constellations of deficits assists in communicating results about discourse measures to a broad audience because it is commonly used and was recently suggested as a core outcome measure for aphasia (Wallace, Worrall, Rose, & Le Dorze, 2016a). Regarding discourse measures, in previous work , we have found high protocol fidelity in the AphasiaBank database across locations and assessors.…”
Section: Absentmentioning
confidence: 97%
“…In addition, as previously mentioned, this study is restricted to measures available in the database, which shaped the approach of dividing by WAB-R subtype. Although we recognize the limitations of the WAB-R, using it as a lens through which to examine differences associated with specific constellations of deficits assists in communicating results about discourse measures to a broad audience because it is commonly used and was recently suggested as a core outcome measure for aphasia (Wallace, Worrall, Rose, & Le Dorze, 2016a). Regarding discourse measures, in previous work , we have found high protocol fidelity in the AphasiaBank database across locations and assessors.…”
Section: Absentmentioning
confidence: 97%
“…A second part of the ROMA project has been to take steps towards obtaining consensus on the actual measurements to be used in aphasia trials (Wallace et al, 2016b), an endeavour shared by the European COST-funded network, Collaboration of Aphasia Trialists (http:// www.aphasiatrials.org). Although the two groups have made different recommendations for the assessment of language functioning, there is concurrence in pointing to the Scenario test (van der Meulen, van de Sandt-Koenderman, Duivenvoorden, & Ribbers, 2010) or the Amsterdam-Nijmegen Everyday Language Test (ANELT) (Blomert, Kean, Koster, & Schokker, 1994) as suggested measures of functional communication (Visch-Brink, 2017).…”
Section: Consensus On Outcome Measures In Aphasia Rehabilitation and The Relevance Of These Measures To Communication Partner Trainingmentioning
confidence: 99%
“…In this second part, two different types of CPT approaches will be used to exemplify issues in measuring outcomes. Third, examples of existing measurements and the proposed ROMA Core Outcome Set (Wallace, Worrall, Rose, & Le Dorze, 2016b) are discussed in relation to the two CPT approaches as well as implications for future measurements.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcomes in aphasia research should be those that are important to people with aphasia and their families (Wallace, 2016). Recent work has shown that these include a range of outcomes across the ICF as well as quality of life and patient satisfaction with treatment (Wallace et al, 2016).…”
Section: Outcome Measuresmentioning
confidence: 99%